DEVELOPMENT OF FABRIC-BASED MICRO PERFORATED PANEL ABSORBER - NOVEMBRIANTY HERMANTO (NIM : 13313041) ; GRADI DESENDRA , MELISSA
The most typical sound absorbers are made of porous material. Although porous material provides decent sound absorption, their fibers can be harmful on health and environment. Thus, micro-perforated panels are considered to be an alternative option to deal with the health and environment issues. However, manufacturing minute holes of the micro perforated panel in Indonesia is not found easily. The use of microstructure of existing materials that is availabe on the market can be alternative to fabricate MPP. A woven fabric is known having microstructure inherently so that will be investigated its potential as MPP material. In this final project, two kinds of woven fabric namely Alabama and Lisburn are employed. For modelling and simulation purposes, the geometrical properties of the woven fabrics are required. Those properties were obtained through measurements using Scanning Electron Microscope (SEM) and subsequenlty used to calculate absorption coefficient of the MPP system consisting of the fabric backing by air cavity by using the Dah-You Maa formula. The results obtained were then validated by measurement results where impedance tube was used to get the absorption coefficients of each fabric. The results show that both of the woven fabric are potential to be used as sound absorbers. For the model itself, the formula proposed by Maa can not be used for all kind of woven fabric especially for fabric that has some fiber in between the pores like Alabama. For this, the resistive screen model derived from JCA (Johnson-Champoux-Allard) model are used. On the other hand, for the case of Lisburn, Maa model is still find to use. It is also foun that the combination of two fabrics to form multilayer system can improve the absorption coefficient, especially in increasing the absorption bandwidth.